(untitled) (Vietnam Journal of Community Medicine, 2022)
Introduction: Endometriosis is a common gynecological disease with painful symptoms including: dysmenorrhea (60-80%), chronic pelvic pain (30-50%), infertility (30-40%) and sexual pain (25-40%). Therefore, endometriosis can more or less affect the quality of a woman’s sex life and sometimes is a direct cause of female sexual dysfunction. Methods: Studies on endometriosis, the effects of the disease on female sexual function and treatment methods were collected from PubMed database. Results: Female sexual dysfunction, mainly sexual pain, is the most commonly described symptom in cases of endometriosis. Meanwhile, therapies for the pain caused by endometriosis are controversial about the effectiveness and duration of symptoms. Discussions: The treatment of symptoms and complications caused by endometriosis currently has not had a great consensus, showing the important role of clinical experts in choosing the regimen for the goal of pain relief, reduce fatigue, improve work productivity and improve quality of life, especially sexual function. Conclusion: Endometriosis is a disease that affects all aspects of a woman’s life, including sexual function.